The Role of Islamic Guidance and Counseling through DHUAR (Dhuha Akbar) Activities in Enhancing the Spiritual Intelligence of Adolescents in Vocational High Schools - Alfiane Suci Setyasri; Aprilia Devi Anggraini (Islamic Religious Education Master Program Universitas Islam Internasional Darullughah Wadda'wah, 2025)
Adolescent spiritual development in vocational high schools faces challenges such as increasing psychosocial problems, weak emotional regulation, and low internalization of religious values, highlighting the need for an integrated and contextual Islamic guidance and counseling model. This study aims to analyze the role of Islamic Guidance and Counseling through the DHUAR (Dhuha Akbar) program in enhancing students’ spiritual intelligence. The study employs a qualitative approach with a case study design at SMKN 2 Kota Tangerang Selatan. Data were collected through in-depth interviews, participant observation, and document analysis, then thematically analyzed using open coding, axial coding, and selective coding to generate core themes. Findings indicate that DHUAR functions as an integrated spiritual development model encompassing ritual, educational, and counseling dimensions. Four key roles of Islamic Guidance and Counseling were identified: construction of spiritual meaning, habituation of religious behavior, enhancement of self-awareness and emotional regulation, and development of spiritual resilience. This intervention improves students’ inner calm, life purpose orientation, prayer discipline, and spiritual coping skills. The study concludes that DHUAR is an effective school-based Islamic counseling intervention for strengthening adolescents’ spiritual intelligence. Its contribution lies in developing a conceptual model of integrated spiritual development, enriching both practice and theory of evidence-based Islamic guidance and counseling.